(untitled) (Lex Journal : Kajian Hukum dan Keadilan, 2025)
Indonesia, with its strategic position as an archipelagic country, is often a transit destination for immigrants, including Rohingya asylum seekers. Increased cross-border access has led to greater human movement between countries so Indonesia is faced with the problem of asylum seekers who want to obtain Human Rights protection. Law Number 39 of 1999 concerning Human Rights regulates the rights of asylum seekers, especially in Article 28 which emphasizes that everyone has the right to seek asylum to obtain political protection from other countries. This study uses a normative research method with the legal sources used consisting of primary, secondary, and tertiary legal materials. This study explores two main legal issues: the scope of legal protection for Rohingya asylum seekers from a human rights perspective, and the intersection of the principle of non-refoulement with Indonesia’s domestic principles. This study shows that the expansion of the doctrine of non-intervention in the ASEAN Charter referring to the UN Charter provides strong legitimacy to provide humanitarian assistance to asylum seekers without violating the sovereignty of the recipient country. Exceptions to the principle of non-refoulement are used so that the receiving state can continue to respect its sovereignty and maintain security and order while remaining committed to protecting human rights.